Effects of different swimming race constraints on turning movements - Veiga, S.; Mallo, J.; Navandar, A.; Navarro, E. (Human Movement Science, 2014)
The aim of this study was to investigate the effects of different swimming race constraints on the evolution of turn parameters. One hundred and fifty-eight national and regional level 200-m (meters) male swimming performances were video-analyzed using the individualized-distance model in the Open Comunidad de Madrid tournament. Turn (p < .001, ES = 0.36) and underwater distances (p < .001, ES = 0.38) as well as turn velocity (p < .001, ES = 0.69) significantly dropped throughout the race, although stroke velocity and underwater velocity were maintained in the last lap of the race (p > .05). Higher expertise swimmers obtained faster average velocities and longer distances in all the turn phases (p < .001, ES = 0.59), except the approach distance. In addition, national level swimmers showed the ability to maintain most of the turn parameters throughout the race, which assisted them in improving average velocity at the end of races. Therefore, the variations in the turning movements of a swimming race were expertise-related and focused on optimizing average velocity. Turning skills should be included in the swimming race action plan.